Effectiveness of the cell block technique in diagnostic cytopathology - Shehnaz Khan; Tanvier Omar; Pamela Michelow (Journal of Cytology, 2012)
Background: One of the constraints of the conventional FNA smear is the limited material available for adjuvant diagnostic investigations including immunocytochemistry. The cell block technique employs the retrieval of small tissue fragments from a FNA specimen which are processed to form a paraffin block. It is widely accepted that cell block technique increases the cellular yield and improves diagnostic accuracy. The ability to obtain numerous tissue sections allows for multiple immunostains and other studies to be performed akin to paraffin sections produced in histopathology. Aims: To determine the effectiveness of the cell block technique by comparing cytomorphological preservation and immunocytochemistry (ICC) stains on paired cell block and conventional fine needle aspiration (FNA) samples. Materials and Methods: In this prospective study, material for both glass slides and cell blocks were collected simultaneously during fine needle aspirates from 47 samples comprising lung and liver masses. Grading of cellularity, morphological preservation, architectural preservation, immunocytochemical staining intensity and presence of background staining on paired FNA smears and cell block samples were compared. Each arm of the paired analysis was performed blindly without knowledge of the grading outcome of the other. The Kappa statistic (κ) was used to measure inter-rater agreement. Results: The 47 samples evaluated included FNAs from the lung, 24/47 (51%) and liver, 23/47 (49%). The immunocytochemistry stains consisted of 44/47 (94%) CK7; 44/47 (94%) CK20; 18/47 (38%) TTF1; 10/47 (21%) synaptophysin; 10/47 (21%) Hepar-1 and 7/47 (15%) AE1/3. There was no overall agreement in preservation of cytomorphological detail and ICC staining between the two methods. The Papanicolaou-stained conventional FNA smears fared better than the cell block for the evaluation of nuclear and morphologic characteristics. The ICC stains worked better on the cell block samples due to lack of background and aberrant staining. Conclusion: Direct FNA smears and cell blocks complement each other and our results indicate that both are needed in the diagnostic work-up of patients. The cost implications of performing both techniques on all FNA material warrants further evaluation.